GAMBARAN KECEMASAN PADA LANSIA DENGAN HIPERTENSI DI KELURAHAN CILENDEK BARAT BOGOR - Tia Amelia Agustin (2020)
Elderly people are susceptible to disease due to aging and health problems. With increasing age the incidence of high blood pressure (hypertension) is higher. Hypertension causes the elderly to experience anxiety due to illnesses suffered by the elderly that never heal. This study aims to describe the description of anxiety in the elderly with hypertension in the Cilendek Barat, Bogor. This research uses descriptive research design to describe or explain the variables studied without analyzing the relationship between variables. The sampling technique uses total sampling with a sample size of 33 respondents. The results of this study were 29 elderly (87.9%) elderly, namely 60-74 years and 4 (12.1%) old age, 75-90 years, 21 respondents (63.6%) and men as many as 12 respondents (36.4%), 18 respondents (54.5%) had hypertension level 1 and as many as 15 respondents (45.5%) had hypertension level 2, anxiety level 3 respondents aged 60-74 years (100%) did not experiencing anxiety or normal, 15 respondents (83.3%) aged 60-74 years and 3 respondents (16.7%) 75-90 years experienced mild anxiety and 11 respondents (91.7%) aged 60-74 years and 1 respondents aged 75-90 years experience moderate anxiety. Researchers suggest that the elderly should increase their awareness of the hypertension they suffer and can reduce anxiety in the elderly and for health workers, especially nurses to pay more attention to the factors that affect the health of the elderly that cause anxiety.